Dialogic learning in collaborative investigation - Alrø, Helle; Skovsmose, Ole (NOMAD Nordic Studies in Mathematics Education, 2004)
This article claims that the quality of classroom communication influences the quality of learning. A dialogue can be seen as a conversation with certain qualities: it is a process of inquiry, includes risk-taking, and maintains equality. These qualities can be observed as dialogic acts. From observing teacher-student and student-student relationships in processes of collaboration we have identified different dialogic acts: getting in contact, locating, identifying, advocating, thinking aloud, reformulating, challenging and evaluating. These acts we include in the Inquiry Co-operation Model (IC-Model). A teaching-learning process rich in dialogic acts in different clusters and combinations provides learning with dialogic qualities. Such learning can emerge in an investigative learning environment. Thus, in this article we develop our understanding of dialogic learning by specifying elements of the IC-Model using an example from the mathematics classroom that takes place in a landscape of investigation.